Tantangan dan Strategi Pencegahan Konflik akibat Intoleransi dan Radikalisme di Era Digital untuk Mewujudkan Keamanan Nasional - Setiawan, Budi; Setiawan, Bayu; Hidayat, Eri R; Widodo, Pujo; Risma Saragih, Herlina Juni; Sukendro, Achmed (Universitas Tribhuwana Tungga Dewi, 2024)
The internet and social media have become effective platforms for spreading extremist ideologies, strengthening polarization, and creating â€œecho chambersâ€ that reinforce radicalism. This research aims to identify the main challenges and formulate strategies to prevent conflicts triggered by intolerance and radicalism in the digital era. Using a qualitative approach with a case study method, this research analyzes secondary data from official documents, previous scientific studies, and social media content to understand the patterns of spreading intolerance and radicalism. The results show that the main challenges in conflict prevention include anonymity and accessibility of technology, social media algorithms that support confirmation bias, lack of digital literacy, weak supervision and regulation, and the appeal of radical ideologies. Therefore, a prevention strategy that involves strengthening digital literacy, improving regulations, and collaboration between stakeholders is considered very important in tackling radicalism in cyberspace. Hopefully, the implementation of this comprehensive strategy can realize a more resilient, inclusive and safe society from the influence of radical ideologies in the digital era. This research implies the need for multi-stakeholder collaboration in developing more effective policies to prevent radicalism in the digital era.Internet dan media sosial menjadi sarana efektif bagi penyebaran ideologi ekstrem, memperkuat polarisasi, dan menciptakan